0773 Why Did Pandemrix Trigger Narcolepsy? A Structural Approach. (27th May 2020) - Peris Sempere, V; Ambati, A; Luo, G; Lin, L; Mignot, E
Abstract: Introduction: The 2009 Pandemrix influenza A pH1N1 vaccine has been linked to an increased number of Narcolepsy type I onsets in children across Europe whereas administration of a very similar adjuvanted vaccine, Arepanrix, had little effects in Canada. One possible explanation for the difference may be vaccine composition differences that could modify peptide binding to narcolepsy associated HLA-DQ0602 allele, as viral extracts for these two vaccines used distinct processes in different factories. Other explanations may involve differences in vaccination timing in relation to the pandemic H1N1 infection wave, or other environmental factors. We have previously compared the amino acid sequence of the Hemagglutinin (HA) component of the Pandemrix and the 2010 Arepanrix vaccine, finding possible contributors, but excluding most of these after DQ0602-tetramer analysis of T cell reactivity in narcolepsy versus controls. Methods: Mass spectrometric characterization of multiple additional batches of Pandemrix and Arepanrix used during 2009 influenza pandemic vaccination campaign was performed. Results: In addition to confirming previously published results such as increased deamidation of hemagglutinin (HA) (146N>D) in Pandemrix (p=2.1e-9), we identified novel differences, including a significant 2-fold post-translation deamidation increase in 277N in Arepanrix versus Pandemrix (p=0.032), together with increased 2-fold glycosylation in the 286-323 positions in Arepanrix (p=0.00036). The 277 N to D/isoD substitution is located in pocket 1 of the binding core of a strong binder NAGSGIIIS, (< 10% rank) for HLA-DQ0602 allele and abolishes epitope binding. The increased glycosylation in Arepanrix occurs in the immediate flanking area of the same 277N epitope and could also reduce DQ0602 presentation of the same epitope through differential binding and/or proteolysis of HA in this region of the molecules. As CD4 T cells recognizing this epitope have been reported to be significantly increased in narcolepsy versus DQ0602 controls, with possible mimicry with homologous hypocretin sequence. Conclusion: These changes could explain why Arepanrix was less narcolepsy inducing. Confirmatory studies, as well as studies of all novel changes observed, are ongoing, but this is a promising result. Support: Wake Up Narcolepsy